2015
DOI: 10.1007/s12017-015-8341-2
|View full text |Cite
|
Sign up to set email alerts
|

NNZ-2566, a Novel Analog of (1–3) IGF-1, as a Potential Therapeutic Agent for Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is the most common form of inherited intellectual disability. Previous studies have implicated mGlu5 in the pathogenesis of the disease, and many agents that target the underlying pathophysiology of FXS have focused on mGluR5 modulation. In the present work, a novel pharmacological approach for FXS is investigated. NNZ-2566, a synthetic analog of a naturally occurring neurotrophic peptide derived from insulin-like growth factor-1 (IGF-1), was administered to fmr1 knockout mice correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…Electrophysiological studies of hippocampal neurons in Fmr1 knockout mice not only confirmed aberrant activation of PI3K/mTOR and MAPK/ERK pathways (Deacon et al, 2015), but also revealed reduced response to excitatory synaptic currents and enhanced glutamate receptor dependent LTD, suggesting the importance of FMRP, PI3K/mTOR and MAPK/ERK pathways, and glutamate receptor functioning underlying deficits in FXS (Braun & Segal, 2000; Huber, Gallagher, Warren, & Bear, 2002). The disruption of neuronal circuitry in Fmr1 knockout mice leads to similar clinical phenotypes of FXS, including anxiety/hyperactivity, impaired short-term and long-term memory, and impaired social interactions (Deacon et al, 2015; Yan, Rammal, Tranfaglia, & Bauchwitz, 2005). …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Electrophysiological studies of hippocampal neurons in Fmr1 knockout mice not only confirmed aberrant activation of PI3K/mTOR and MAPK/ERK pathways (Deacon et al, 2015), but also revealed reduced response to excitatory synaptic currents and enhanced glutamate receptor dependent LTD, suggesting the importance of FMRP, PI3K/mTOR and MAPK/ERK pathways, and glutamate receptor functioning underlying deficits in FXS (Braun & Segal, 2000; Huber, Gallagher, Warren, & Bear, 2002). The disruption of neuronal circuitry in Fmr1 knockout mice leads to similar clinical phenotypes of FXS, including anxiety/hyperactivity, impaired short-term and long-term memory, and impaired social interactions (Deacon et al, 2015; Yan, Rammal, Tranfaglia, & Bauchwitz, 2005). …”
Section: Resultsmentioning
confidence: 88%
“…Treatment of Fmr1 knockout mice with NNZ-2566 resulted in normalization of phosphor-ERK and phosphor-Akt levels and reduction of dendritic spine neurons, indicating a reversal of MAPK/ERK and PI3K/mTOR signaling abnormalities and correction of dendritic spine morphology. The Fmr1 knockout mice also displayed lower anxiety levels, reduced hyperactivity, improved short-term and long-term memory, improvement in learning and LTP, and normalized social recognition and behaviors (Deacon et al, 2015). The lack of adverse events and positive therapeutic profile in preclinical trials with Fmr1 mice provides evidence for IGF-1 as a potential therapeutic agent in FXS and there is an ongoing clinical trial in phase II with the IGF-1 analogue, NNZ-2566.…”
Section: Resultsmentioning
confidence: 99%
“…While our methodology utilizes a readily available biological sample that can be accessed across a wide functioning range of persons with autism, we cannot be sure that enhanced ERK activation in peripheral lymphocytes equates with ERK dysregulation in brain where we would expect molecular perturbation to result in an autism phenotype. Despite this, in recent study in the knockout mouse model of FXS, excessive ERK activation was noted in both brain and blood cell samples showing that some correlation may exist (Deacon et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…In 2001, there was one published open-label trial of cerebrolysin, a neuropeptide preparation that includes nerve growth factors [94]. Recently, there have been several trials of full-length recombinant IGF-1 and an active tripeptide component of IGF-1 (trofinetide) that may have a greater effect on glial processes [104]. There are also ongoing trials of two BDNF-boosters, glatiramer acetate and fingolimod (ClinicalTrials.gov identifiers NCT02153723, NCT02061137).…”
Section: Drugs Tested In Rtt Trialsmentioning
confidence: 99%